2018
DOI: 10.3390/s18061687
|View full text |Cite
|
Sign up to set email alerts
|

FEM Analysis of Sezawa Mode SAW Sensor for VOC Based on CMOS Compatible AlN/SiO2/Si Multilayer Structure

Abstract: A Finite Element Method (FEM) simulation study is conducted, aiming to scrutinize the sensitivity of Sezawa wave mode in a multilayer AlN/SiO2/Si Surface Acoustic Wave (SAW) sensor to low concentrations of Volatile Organic Compounds (VOCs), that is, trichloromethane, trichloroethylene, carbon tetrachloride and tetrachloroethene. A Complimentary Metal-Oxide Semiconductor (CMOS) compatible AlN/SiO2/Si based multilayer SAW resonator structure is taken into account for this purpose. In this study, first, the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
0
21
1
Order By: Relevance
“…The sensors showed a sensitivity that ranges from 0.75 to 12 Hz/ppm for the Rayleigh mode, and from 1.57 to 25 Hz/ppm for the Sezawa mode. These sensitivity values are lower than those referred to our structure for both the Rayleigh and Sezawa modes at λ = 10 µm; moreover, our structure is based on fixed ZnO and SiO 2 layers' thicknesses, as opposed to the case described in reference [23] where different AlN and SiO 2 layers' thicknesses are required to excite the Rayleigh wave (both AlN and SiO 2 are 2 µm thick) and the Sezawa wave (AlN and SiO 2 are 2 and 3 µm thick).…”
Section: Gas Sensing Simulationcontrasting
confidence: 56%
See 2 more Smart Citations
“…The sensors showed a sensitivity that ranges from 0.75 to 12 Hz/ppm for the Rayleigh mode, and from 1.57 to 25 Hz/ppm for the Sezawa mode. These sensitivity values are lower than those referred to our structure for both the Rayleigh and Sezawa modes at λ = 10 µm; moreover, our structure is based on fixed ZnO and SiO 2 layers' thicknesses, as opposed to the case described in reference [23] where different AlN and SiO 2 layers' thicknesses are required to excite the Rayleigh wave (both AlN and SiO 2 are 2 µm thick) and the Sezawa wave (AlN and SiO 2 are 2 and 3 µm thick).…”
Section: Gas Sensing Simulationcontrasting
confidence: 56%
“…The behavior of the Si/SiO 2 /ZnO SAW devices operating as gas sensors was studied by 2D FEM with Ansys software, under the hypothesis that the surface of the ZnO layer is covered with a thin polyisobutylene (PIB) film, 0.8 µm thick. The sensor was investigated for the detection of the following five volatile organic compounds at atmospheric pressure and room temperature: dichloromethane (CH 2 Cl 2 ), trichloromethane (CHCl 3 ), carbontetrachloride (CCl 4 ), tetrachloroethylene (C 2 Cl 4 ), and trichloroethylene (C 2 HCl 3 ) [23,24]. The PIB interaction with the gas molecules, i.e., the sensing mechanism, was simulated as an increase in mass density, ρ = ρ unp + ∆ρ, being ρ unp the unperturbed mass density of the PIB layer (in air) and ∆ρ the partial density of the gas molecules adsorbed in the PIB layer, ∆ρ = K•M•c 0 •P/RT, where P and T are the ambient pressure and temperature (1 atm and 25 • C), c 0 is the gas concentration in ppm, K = 101.4821 is the air/PIB partition coefficient for the studied gas, M is the molar mass, and R is the gas constant [24][25][26][27].…”
Section: Gas Sensing Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Water (ρc = 1000 kg/m3 and C = 1500 m/s) was opted for to be placed in the fluid domain and was considered as a Newtonian fluid in order to simplify the calculation due to the presence of viscosity. In the previous study, it has been demonstrated that Sezawa mode could give clear advantage for gas sensing compared to typical Rayleigh SAW by producing a higher resonance frequency shift [27]. Nevertheless, it is ambiguous whether the Sezawa mode operating in the liquid environment can produce a similar effect.…”
Section: Simulation Of Surface Wave Phase Velocitymentioning
confidence: 99%
“…Therefore, this study chose to investigate SAW-based gas sensors as they are not only highly sensitive and offer faster disease detection but are environmentally friendly as well. The ability to introduce a sensing layer further enhances its performance in terms of sensitivity and selectivity as it enables mass loading that results in changes in acoustic wave velocity and resonant frequency [6]. This study aims to thoroughly investigate the performance of polymer-based sensing layers in SAW-based gas sensors through simulation via the finite element method (FEM).…”
Section: Introductionmentioning
confidence: 99%